KEBIJAKAN PEMERINTAH TENTANG PENJAMINAN MUTU PENDIDIKAN - Rahmat Hidayat; Herwadi Herwadi; Nuri Rahmadani (Universitas Dharmawangsa, 2020)
The education quality policy refers to the eight SNPs, namely: Content Standards, Process Standards, Graduates Competency Standards, Educators and Education Personnel Standards, Management Standards, Facilities and Infrastructure Standards, Financing Standards, Assessment Standards. Each of the eight National Education Standards has its own policy. To measure the implementation of national quality standards that cover 8 (eight) national education standards, measurement of the achievement of reference standards and evaluation of education quality is carried out on educational units / programs through: 1). Self Evaluation Unit / Educational Program (EDS); 2). Monitoring Unit / Education Programs by Local Governments (MSPD); 3). Accreditation; 4). Certification; 5). National exam; and 6). Database and Information Data Collection